IMPACT OF HUMAN CAPITAL CAPABILITIES ON KNOWLEDGE MANAGEMENT PROCESS - Kaldeen, Mubarak; Nawaz, Samsudeen Sabraz (International Journal of Psychosocial Rehabilitation, 2020)
Human capital of organisations are one of the key successful Knowledge Management (KM) enablers. Since tacit knowledge resides in the minds of employees, they are at the heart of creating knowledge in an organisation. Moreover, employee interaction in an organisation is an important source of intangible value in the intellectual assets. Therefore, the objective of this study to analyse the impact of human capital capabilities on knowledge management process (KMP). Probability sampling method was employed and questionnaire survey carried out among private sector businesses in Sri Lanka. 243 usable responses were received and results of statistical analysis of the responses revealed that human capital has significant impact on knowledge management process. Managers need to exploit the human capital capacity and should encourage innovation and application of knowledge, thus human capital become specialized asset for on the organisations.